Neutrophil extracellular traps and DNases orchestrate formation of peritoneal adhesions - Elrod, Julia; Heuer, Annika; Knopf, Jasmin; Schoen, Janina; Schönfeld, Lavinia; Trochimiuk, Magdalena; Stiel, Carolin; Appl, Birgit; Raluy, Laia Pagerols; Saygi, Ceren; Zlatar, Leticija; Hosari, Sami; et al. (iScience, 2023)
Peritoneal adhesions are poorly understood but highly prevalent conditions that can cause intestinal obstruction and pelvic pain requiring surgery. While there is consensus that stress-induced inflammation triggers peritoneal adhesions, the molecular processes of their formation still remain elusive. We performed murine models and analyzed human samples to monitor the formation of adhesions and the treatment with DNases. Various molecular analyses were used to evaluate the adhesions. The experimental peritoneal adhesions of the murine models and biopsy material from humans are largely based on neutrophil extracellular traps (NETs). Treatment with DNASE1 (Dornase alfa) and the human DNASE1L3 analog (NTR-10), significantly reduced peritoneal adhesions in experimental models. We conclude that NETs serve as essential scaffold for the formation of adhesions; DNases interfere with this process. Herein, we show that therapeutic application of DNases can be employed to prevent the formation of murine peritoneal adhesions. If this can be translated into the human situation requires clinical studies.
Online verfügbar: 27. OKtober 2023, Artikelversion: 10. November 2023
Gesehen am 08.04.2024